PENGARUH ECONOMIC VALUE ADDED, RASIO PROFITABILITAS DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014 – 2018 - NOVI CHOKY; FENNY .; EDY FIRMANSYAH; METYRIA IMELDA HUTABARAT (JURNAL ILMIAH MAKSITEK, 2020)
This research was conducted at Insurance Companies Listed on the Indonesia Stock Exchange. The purpose of this studywas to determine the effect of Economic Value Added, Profitability Ratios, and Earning Per Share on share prices oninsurance companies on the Indonesia Stock Exchange. The research approach used in this study is a quantitativeapproach. This type of research used in this research is quantitative descriptive. The nature of this research is descriptiveexplanatory. The population to be used in this study is 14 (fourteen) financial statements of insurance companies listed onthe Indonesia Stock Exchange in 2014-2018. Company samples were 10 (ten) companies. Data collection techniques arelibrary and documentation study. Variables are measured by Ratio scale. The data analysis method used is multiple linearregression analysis. The results of the study prove that EVA (Economic Value Added) has no positive and no significanteffect on stock prices on Insurance Companies Listed on the Indonesia Stock Exchange in 2014-2018. Profitability Ratioshave no negative and no significant effect on stock prices on Insurance Companies Listed on the Indonesia Stock Exchangein 2014-2018. Earning Per Share has a positive and significant effect on stock prices on Insurance Companies Listed on theIndonesia Stock Exchange in 2014-2018. Economic Value Added, Profitability Ratios, and Earning Per Share havesignificant and significant effect on share prices on Insurance Companies Listed on the Indonesia Stock Exchange in 2014-2018.